PENGARUH PERUBAHAN KEBIJAKAN DEVIDEN TERHADAP PERUBAHAN KINERJA KEUANGAN DENGAN PERUBAHAN RASIO AKTIVITAS SEBAGAI VARIABEL INTERVENING - Magdalena Nany; Trisni Suryarini Maria (Jurnal Akuntansi Bisnis, 2011)
Lower dividend distribution will increase retained earnings. Higher assets will increase financial per.formance if the assets is well managed. The objective of this research was to examine whether activity ratio's changes is a mediator on the association between dividend policy' changes and financial performance's changes or not. F((ty nine companies listed at Jakarta Stock Exchange at the end 0.( 2004 that distributed their dividends for 2004 and 2004, were analyzed by path analysis. The results show that activity ratio's changes isn't a mediator on the association between dividend policy' changes and financial performance's changes.